Real-space imaging of nucleation and size induced amorphization in PdSi nanoparticles. (July 2016) - Sun, Y.T.; Cao, C.R.; Huang, K.Q.; Shi, J.A.; Zhao, L.Z.; Li, M.Z.; Bai, H.Y.; Gu, L.; Zheng, D.N.; Wang, W.H.
Abstract: Nucleation has been studied for hundreds of years and can be described by classical nucleation theory (CNT) in many cases. However, the understanding of nucleation has been limited by its short time and small size scale, which causes substantial experimental challenges in direct visualization of the nucleation process. Here, using double-aberration-corrected scanning transmission electron microscope, we show the real space imaging of the atomic level nucleation process and the evolution of nucleus in PdSi nanoparticles produced by pulsed laser deposition. Critical nucleus size, indicated by a structural transition from amorphous to crystal, is clearly observed and found to be in consistent with CNT prediction. We also show that the nano-scale nucleation process is analogous with size induced amorphization process which is confirmed by the molecular dynamics simulation. Graphical abstract: Highlights: Direct atomic level observation in real space of nucleation process. The confirmation of the classical nucleation theory in atomic scale. Effects of temperature and size in the amorphization process.